2016
DOI: 10.1136/bmjopen-2015-010665
|View full text |Cite
|
Sign up to set email alerts
|

How different are baby-led weaning and conventional complementary feeding? A cross-sectional study of infants aged 6–8 months

Abstract: ObjectivesTo compare the food, nutrient and ‘family meal’ intakes of infants following baby-led weaning (BLW) with those of infants following a more traditional spoon-feeding (TSF) approach to complementary feeding.Study design and participantsCross-sectional study of dietary intake and feeding behaviours in 51 age-matched and sex-matched infants (n=25 BLW, 26 TSF) 6–8 months of age.MethodsParents completed a questionnaire, and weighed diet records (WDRs) on 1–3 non-consecutive days, to investigate food and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
8
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(192 citation statements)
references
References 24 publications
14
156
8
14
Order By: Relevance
“…Although we did not assess the energy density of the foods offered, only 2% of infants from the BLW group were underweight according to WHO growth charts . Furthermore, Morison et al ., in their small sample study, reported that energy intake was similar between the BLW and traditional feeding styles . In contrast to low‐energy purees, which are frequently made of fruits or vegetables, finger foods, if carefully chosen, can be very nutrient dense, therefore an infant who appears to be eating little when self‐feeding may potentially be closer to meeting their nutrient requirements.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although we did not assess the energy density of the foods offered, only 2% of infants from the BLW group were underweight according to WHO growth charts . Furthermore, Morison et al ., in their small sample study, reported that energy intake was similar between the BLW and traditional feeding styles . In contrast to low‐energy purees, which are frequently made of fruits or vegetables, finger foods, if carefully chosen, can be very nutrient dense, therefore an infant who appears to be eating little when self‐feeding may potentially be closer to meeting their nutrient requirements.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, BLW mothers were more likely to breast‐feed their infants exclusively to 6 months, and wait until 6 months to introduce solids. The baby‐led approach to weaning has also been identified as the strongest predictor of weaning (introduction of complementary foods) at the recommended age …”
Section: Discussionmentioning
confidence: 99%
“…Comparison of intake at 7 months [23 •• ] and 12 months [24] found no significant difference in energy intake between the two groups.…”
Section: Is There a Difference In Diet Consumed?mentioning
confidence: 99%
“…The standard practice of exposing the infant to new flavors, smells, tastes, and textures through spoon-feeding by an adult may not be the only or the best strategy. A baby-led approach to feeding has been advocated in which advances in CF are determined and directed by the baby, relying on the child's curiosity [46][47][48][49] . This type of self-feeding mirrors the strategy used by Clara Davis in her landmark studies on toddler self-feeding in the 1920s [50] .…”
Section: The Introduction To Complementary Feeding: 6-12 Monthsmentioning
confidence: 99%